ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS - Arieany Widya Deviacita; Tarmizi Achmad (Diponegoro Journal of Accounting, 2013)
The purpose of this study was to analyze the influence of corporate governance mechanism on financial distress. Corporate governance mechanism in this study include the ownership structure, board size, independent board, board activity, and the audit committee expertise. This study used 141 sample companies consist of 34 financially distressed firms and 107 non financially distressed firms. Data obtained by using a purposive sampling method of manufacturing companies which were listed on Indonesia Stock Exchange (IDX) during 2006-2010. The financial distress criteria in this study were measured by using Z-score on financial distress prediction models of Altman (1968). The data has analyzed by using multiple regression method. The results showed that directors ownership, institutional ownership, and audit committee expertise has negatively affected financial distress, while this study failed to prove the influence of board size, independent board, and board activity on financial distress.